Nanocellulose-A Sustainable and Efficient Nanofiller for Rubber Nanocomposites: From Reinforcement to Smart Soft Materials. (7th June 2022) - Cao, Liming; Huang, Jiarong; Fan, Jianfeng; Gong, Zhou; Xu, Chuanhui; Chen, Yukun
Abstract: With increasing ecological and environmental concerns, the development of materials and products from renewable and sustainable resources is of great public value. Due to the renewability, abundance, and biodegradability, etc., nanocellulose have proven to be one of the most attractive and promising sustainable alternatives of modern and future times. Many exciting applications of nanocellulose have been explored, especially in the fabrication of polymer nanocomposites. As a particular class of polymer, here, we present a comprehensive overview of the current development of nanocellulose in rubber nanocomposites. In particular, this review assembles the use of nanocellulose as reinforcing phase in improving the mechanical and other properties of rubbers, as well as the efforts to improve the dispersion of nanocellulose in the matrix and enhance the interfacial interactions between them. The unique features of nanocellulose used in functional/stimuli-responsive rubbers, such as sensors, self-healing materials, and shape memory materials, as well as its utilization as bio-template agents by taking full advantage of its active surface and high aspect ratio are also discussed in this review. Finally, we evaluate the challenges encountered in current research and highlight future opportunities for the high-performance and tunable performances of nanocomposites composed of elastomers and nanocellulose. Graphical Abstract: UF0001